IMPLEMENTASI PEMBELAJARAN MENDALAM MELALUI REALISTIC MATHEMATICS EDUCATION BAGI GURU SD DI KOTA AMBON - Mananggel, Marlin Blandy; Laurens, Theresia; Kempa, Vicardy (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Merdeka Curriculum emphasizes the importance of deep learning as an effort to enhance students’ conceptual understanding, particularly in mathematics education. However, its implementation in elementary schools still faces various challenges, especially related to teachers’ limited understanding in designing and conducting meaningful learning experiences. This community service program aims to improve the pedagogical competencies of elementary school teachers in Ambon City through training and mentoring on the implementation of Realistic Mathematics Education (RME) as an approach to achieving deep learning. The program consisted of four stages: planning, implementation, evaluation, and reflection. The implementation methods included lectures, question-and-answer sessions, discussions, and guided discovery practices. The results show an improvement in teachers’ understanding of deep learning through the application of RME in mathematics teaching, particularly in the domains of number and geometry. The training was rated highly in terms of participant enthusiasm throughout the process and based on satisfaction questionnaire responses. Teachers are expected to design deep learning activities that apply RME principles, involving students as active learning agents, incorporating students’ real-life experiences, and encouraging further exploration and mathematical reasoning. Thus, this program provides a positive contribution to the improvement of the quality of mathematics learning in elementary schools and supports the implementation of the Merdeka Curriculum in Ambon City.